IMPROVEMENT OF FERTILIZATION NORMS IN THE CULTIVATION OF STRAWBERRY IN CLOSED AREAS - Omonova Malika Mamasoat kizi (Web of Journals Publishing, 2025)
This article highlights the issue of improving fertilizer application rates for growing strawberries in enclosed areas. The biological characteristics of strawberry plants, agrotechnical requirements, adaptation of varieties to soil and climatic conditions, and the need for various types of fertilizers were analyzed. In particular, the effectiveness of fruit cultivation in greenhouse conditions was studied using the example of the "Kulver" and "Tashkent" varieties. The amount of nitrogen, phosphorus, and potassium fertilizers applied during the growing season, the stages of their assimilation, and their impact on the yield are scientifically substantiated. The possibilities of growing products throughout the year based on hydroponics technology were also considered. The research results will be of great practical importance in the implementation of intensive technologies in the horticulture sector of the republic.
Keywords: Strawberry, field, agricultural techniques, fertilizer application rate, nitrogen, phosphorus, potassium, greenhouse, hydroponics, varieties, yield, fruit crops.